Interrelationship of Osteopontin, MMP-9 and ADAMTS4 in Patients With Osteoarthritis Undergoing Total Joint Arthroplasty - Slovacek, Hannah; Khanna, Rajan; Poredos, Pavel; Jezovnik, Mateja; Hoppensteadt, Debra; Fareed, Jawed; Hopkinson, William (Clinical and applied thrombosis/hemostasis, 2020)
Osteoarthritis (OA) is a degenerative joint disease characterized by loss of articular cartilage, inflammation and pain, which sometimes necessitates total joint arthroplasty (TJA). Profiling biomarkers of cartilage degradation and inflammation is a promising area of research to understand the pathogenesis of OA. This study aims to report the post-operative fluctuations of 3 biomarkers of OA, osteopontin (OPN), matrix metalloproteinase-9 (MMP-9), and ADAMTS4 (a disintegrin and metalloproteinase with thrombospondin motifs 4), in patients undergoing TJA to further define the interaction among these biomarkers and delineate their role in OA pathogenesis. OPN is an extracellular matrix (ECM) glycoprotein with increased activity in OA and joint damage and is upregulated by either inflammation or cleavage by MMPs and thrombin. MMP-9 is known to cleave OPN and is upregulated by inflammatory markers, such as IL-1, IL-6 and CRP. ADAMTS4 is an enzyme that degrades aggrecan, a major component of cartilage. These biomarkers were measured in deidentified blood samples collected on the day of surgery, 1 day post-operatively, and day 5-7 post-operatively. MMP-9 and OPN levels were significantly elevated at all times, and ADAMTS4 was significantly decreased at baseline versus controls. OPN and ADAMTS4 inversely fluctuated post-operatively, indicating an interrelation between these 2 biomarkers. This study suggests that the upregulation of MMP-9 and therefore OPN then results in the downregulation of ADAMTS4. The relationship between OPN and thrombin also highlights the importance of monitoring for thrombotic complications. These biomarkers, along with thrombin-mediated cleavage products, may be helpful in the prognostic management of OA patients.